2016
DOI: 10.22256/pubvet.v7n1.1485
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive profile of a rural canine population in Juerana Village, Aritaguá district, city of Ilhéus, Bahia, Brazil, 2012.

Abstract: In rural communities, dogs provide important and essential roles, such as hunters, companions and security. Often, dog owners lack sufficient knowledge of canine management or are indifferent to their dogs’ well-being resulting in the spread of diseases to human, animal and the surrounding environment. A semi-structured questionnaire survey was taken, in March 2012, in order to determine the canine population profile of Juerana Village, the socio-economic profile of the dog owners and evaluate and analyze whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Throughout the year, the Village of Juerana receives tourists from diverse places who enjoy the bars and restaurants scattered throughout the village, especially on the banks on the Rio Almada. In this context, the risk factors identified by us and others, such as high number of semi-restricted infested dogs (94.4%), the lack of paved streets, poor hygiene and below average socioeconomic conditions as observed by Harvey et al (2013), put the residents as well as the tourists at risk of disease. Many national and international tourists are infested while traveling to and within Brazil.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Throughout the year, the Village of Juerana receives tourists from diverse places who enjoy the bars and restaurants scattered throughout the village, especially on the banks on the Rio Almada. In this context, the risk factors identified by us and others, such as high number of semi-restricted infested dogs (94.4%), the lack of paved streets, poor hygiene and below average socioeconomic conditions as observed by Harvey et al (2013), put the residents as well as the tourists at risk of disease. Many national and international tourists are infested while traveling to and within Brazil.…”
Section: Discussionmentioning
confidence: 77%
“…In March 2012, a previous descriptive study of the canine population of the Village of Juerana showed a dog to human ratio of 1:3.7 (Harvey et al, 2013). In this paper, considering the same human population of that time with the recent number of dogs found (114) in the 104 surveyed households, this ratio would be 1:3.2, reaffirming the high number of dogs on the site, perpetuating the risk of infestation for people living and visiting that community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of cats with access to the street is higher than that of dogs, which may be a determining factor in the low proportion of animals over 4 years old, suggesting a lower longevity of cats in the municipality. The number of semi domesticated animals may be a factor in reducing the rates of elderly peo since animals with free access to the street are less long-lived when compared to domiciled ones, as they are subject to the risk of being run over, attacked and poisoned Cardoso, 2012). We believe that the number of dogs and cats with access to the street, associated with a high rate of animals with reproductive potential, leads to the rate of young individuals observed.…”
Section: Resultsmentioning
confidence: 91%
“…The project was developed in a semi-rural endemic coastal community frequented by tourists (Figure 1), Vila Juerana, located in the district of Aritagua, part of the municipality of Ilheus, Bahia, Brazil (S 14.96767 • , W 039.32436 • ) [37]. The predominant vegetation type is Atlantic Forest, with the presence of beaches and mangrove forests.…”
Section: Ethical Considerations and Study Areamentioning
confidence: 99%